Interictal balance changes in migraine- A stabilometric and diffusion tensor imaging study - P. Q. F. Góes, Cristiana; Fontana, Ana Paula; V. Silva, Isadora (Brazilian Journal of Health and Biomedical Sciences, 2025)
Cerebellar dysfunctions have been found in migraineurs, while ischemic lesions have been described to be more frequent in their posterior fossa. To examine balance abnormalities and anatomical cerebellar changes in migraine interictally, 48 patients (21 with aura — MWA; 27 without aura — MWoA) underwent an evaluation of their stance by computerized static stabilometry (CSS) and were compared with controls. The frequency and amplitude of swaying in both the anteroposterior and latero-lateral axes, as well as the area and velocity of oscillations were estimated with open and closed eyes. A subgroup of 10 individuals and 10 controls was also examined with MRI and diffusion tensor imaging. Fraction anisotropy (FA) was obtained in nine regions of interest at the posterior fossa. Clinical parameters (age, age at onset, timespan of disease and frequency of attacks) were correlated with FA and CSS data. Subclinical impairment with greater lateral axis oscillation, especially in MWA, was observed. MWA patients were more dependent on visual input to control lateral sway than MWoA subjects. The anatomy of the cerebellum, especially at the dentate nuclei and middle cerebellar peduncles was comparatively impaired in migraine sufferers, as estimated by FA.